Absorption of anionic surfactant on surface of reservoir minerals in alkaline-surfactant-polymer system / Tengku Amran Tengku Mohd … [et al.] - Tengku Mohd, Tengku Amran; Abdul Wahib, Muhammad Ikhram; Nik Ab Lah, Nik Khairul Irfan; Mat Shayuti, Muhammad Shafiq; Shahruddin, Munawar Zaman; Mohd Zin, Rohani; Jaafar, Mohd Zaidi (Universiti Teknologi MARA, 2021)
Alkaline-surfactant-polymer (ASP) flooding is significant to the oil and gas industry due to synergistic interaction between alkaline, surfactant and polymer. However, chemical losses due to adsorptions of surfactant and polymer on the rock surface could lead to inefficiency of the process. There are also significant uncertainties on adsorption mechanism when surfactant is flooded with presence of alkaline and polymer. This study highlights the static adsorption tests using anionic sodium dodecyl sulphate (SDS), hydrolysed polyacrylamide (HPAM) and sodium carbonate (Na2CO3) as the surfactant, polymer and alkaline, respectively. Sand particles and kaolinite clay were used as the reservoir minerals. The adsorption tests were conducted at various surfactant concentrations ranging from 50 to 2000 ppm. Sodium chloride (NaCl) concentration was investigated from 0 to 2 wt.%, while the local sand and kaolinite was mixed in surfactant solution at a fixed mass to volume ratio of 1:5. The static adsorption test was conducted by shaking the mixture samples and centrifugation before analysing the supernatant liquid using UV-Visible spectrophotometer. The results showed that the surfactant adsorption was higher on kaolinite compared to sand particle. The higher the salinity, the higher the adsorption of surfactant due to higher ionic strength. The adsorption of SDS surfactant on sand particles and kaolinite was lesser in ASP system compared to the presence of surfactant solution alone. Thus, it can be concluded that the presence of polymer and alkaline in ASP solution have great potential to reduce the surfactant adsorption on both sand particle and kaolinite.